Featured Cover. (9th October 2020) - De la Cadena, Alejandro; Valensise, Carlo M.; Marangoni, Marco; Cerullo, Giulio; Polli, Dario
Abstract : The cover image is based on the Special Issue – Research Article Broadband stimulated Raman scattering microscopy with wavelength‐scanning detection by Alejandro De la Cadena et al., https://doi.org/10.1002/jrs.5816 .